The determinants of electronic payment systems usage from consumers' perspective - Oney, Emrah; Guven, Gizem Oksuzoglu; Rizvi, Wajid Hussain (Routledge Journals, Taylor & Francis Ltd, 2017)
Electronic Payment Systems (EPS) have been improving individuals' quality of life through providing ease of payment for online transactions. The effects of trust and security on the use of EPS have long been recognised in e-commerce literature. However, very few studies have examined these two concepts from the viewpoint of users. This study has developed a conceptual model to examine the determinants of perceived security and trust as well as the impact of perceived security and trust on the use of EPS. A sample of 299 respondents was analysed through structural equation modelling (SEM); the findings indicate that both perceived security and trust have a significant influence on EPS use. Technical protection and past experience have been found to be the common determinants of perceived security and trust. Managerial implications of the findings are discussed in light of the study's limitations and suggestions for further research indicated.
Keywords: Perceived trust; perceived security; past experience; electronic payment systems (EPS); structural equation modelling; SEM analysis